2015
DOI: 10.1007/s11356-015-4927-3
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic and genotoxic effects of abamectin, chlorfenapyr, and imidacloprid on CHOK1 cells

Abstract: The cytotoxicity and genotoxicity of abamectin, chlorfenapyr, and imidacloprid have been evaluated on the Chinese hamster ovary (CHOK1) cells. Neutral red incorporation (NRI), total cellular protein content (TCP), and methyl tetrazolium (MTT) assays were followed to estimate the mid-point cytotoxicity values, NRI50, TCP50, and MTT50, respectively. The effects of the sublethal concentration (NRI25) on glutathione S-transferase (GST), glutathione reductase (GRD), glutathione peroxidase (GPX), and total glutathio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 74 publications
2
21
0
4
Order By: Relevance
“…Another commercial insecticide containing imidacloprid was used in a study on human hepatocellular carcinoma (HepG2) cells where increased cytotoxicity and increased level of DNA damage were observed after 24-h exposure (Bianchi et al 2015). The cytotoxicity of imidacloprid in vitro has also been investigated in Chinese hamster ovary cells (Al-Sarar et al 2015) and in a cell line based on gill cells from Paralichthys olivaceus (Su et al 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another commercial insecticide containing imidacloprid was used in a study on human hepatocellular carcinoma (HepG2) cells where increased cytotoxicity and increased level of DNA damage were observed after 24-h exposure (Bianchi et al 2015). The cytotoxicity of imidacloprid in vitro has also been investigated in Chinese hamster ovary cells (Al-Sarar et al 2015) and in a cell line based on gill cells from Paralichthys olivaceus (Su et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…While the toxicity of neonicotinoids in honeybees has been investigated extensively, studies on material of human origin seem sparse, especially when it comes to nitenpyram. Whereas there are some in vitro studies of the cytotoxicity of imidacloprid in human cells (Al-Sarar et al 2015;Bianchi et al 2015;Calderon-Segura et al 2012;Senyildiz et al 2018;Zeljezic et al 2016)-no similar studies of nitenpyram were found in our literature search. A similar picture emerges when it comes to genotoxicity studies of imidacloprid and nitenpyram.…”
Section: Introductionmentioning
confidence: 88%
“…Today, they make one third of the global insecticide market. Among them imidacloprid was the world's top selling insecticide in 2010 (33). In spite of the original belief that neonicotinoids are only mildly toxic to mammals, there is increasing evidence of a variety of toxic effects on animals and humans (34)(35)(36)(37).…”
Section: Neonicotinoidsmentioning
confidence: 99%
“…Dentre os diversos eventos negativos, destaca-se a capacidade de muitos pesticidas desencadear eventos mutagênicos e carcinogênicos (Demsia et al, 2007;Hong et al, 2017;Tariba-Lorakovic et al, 2017;Gonçaves et al, 2017;Santo et al, 2018), incluindo inseticidas (Arcaute et al, 2014;Atli-Skeroglu et al, 2018;Khan et al, 2018;Calderon-Segura et al, 2018). (Feng et al, 2004;Demsia et al, 2007;Costa et al, 2009;Behinder et al, 2012;Pérez-Iglesias et al, 2014;Bagri et al, 2014;2016;Bianchi et al, 2015;2016;Al-Sarar et al, 2015;Arslan et al, 2015;Kataria et al, 2015;Stivaktakis et al, 2016;Iturburu et al, 2016;Hong et al, 2018;Muzinic et al, 2018;Yucel e Kavis et al, 2018;Guo et al, 2018. Guo et al (2018 avaliaram os efeitos de IMI em células linfoblastos TK6 e identificaram danos de natureza mutagênica e genotóxica nas concentrações de 0,1; 1; 5 e 10 µg/mL, por meio do teste do micronúcleo (TMN) e o ensaio cometa.…”
Section: Detecção De Mutação E Recombinaçãounclassified
“…Pesticidas apesar de serem correlacionados com toxicidade seletiva em pragas no campo, também são capazes de interagir com biomoléculas de espécies não alvas de combate, podendo desencadear efeitos toxicológicos em diferentes níveis na biota, incluindo humanos (Mondal et al, 2012). Do ponto de vista ocupacional, pesticidas são preocupantes devido a magnitude da contaminação em um contexto global, partindo da premissa que o homem está exposto diariamente a diferentes concentrações, por meio da ingestão dos alimentos contendo resíduos de diferentes agroquimicos (Al-Sarar et al, 2015).…”
Section: Introductionunclassified